Toward the Future of Early Intervention for Adult Hearing Loss - Johnson, Carole E.; Barbee, Christi M.; Danhauer, Jeffrey L.; Jilla, Anna Marie; Kimball, Suzanne H.; Seever, Katie L. (Seminars in Hearing, 2018)
This issue of Seminars in Hearing has focused on the early intervention of adult sensorineural hearing loss (SNHL). Contributions to this monograph have taken a contemporary issues approach to the prevention, diagnosis, and treatment of mild SNHL. This article looks toward the future and discusses clinical and research implications for the early intervention of adult SNHL.
Keywords: adults; early intervention; hearing loss